1999
DOI: 10.1073/pnas.96.25.14482
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic potential of stem cells isolated from murine skeletal muscle

Abstract: We have discovered that cells derived from the skeletal muscle of adult mice contain a remarkable capacity for hematopoietic differentiation. Cells prepared from muscle by enzymatic digestion and 5-day in vitro culture were harvested, and 18 ؋ 10 3 cells were introduced into each of six lethally irradiated recipients together with 200 ؋ 10 3 distinguishable whole bone marrow cells. After 6 or 12 weeks, all recipients showed high-level engraftment of muscle-derived cells representing all major adult blood linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
600
3
11

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 854 publications
(627 citation statements)
references
References 44 publications
13
600
3
11
Order By: Relevance
“…Furthermore, recent studies have reported that these cells may exist in skeletal muscle. 7,9,[23][24][25][26][27][28][29] The presence of stem cells in skeletal muscle makes this tissue an attractive source of cells that are capable of enhancing the healing of various tissues. 9 In fact, we have recently observed that the genetic engineering of MDC (mc13) to express rhBMP-2 can be used to enhance closure of a non-healing skull defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies have reported that these cells may exist in skeletal muscle. 7,9,[23][24][25][26][27][28][29] The presence of stem cells in skeletal muscle makes this tissue an attractive source of cells that are capable of enhancing the healing of various tissues. 9 In fact, we have recently observed that the genetic engineering of MDC (mc13) to express rhBMP-2 can be used to enhance closure of a non-healing skull defect.…”
Section: Discussionmentioning
confidence: 99%
“…23 It is now well established that muscle satellite cells are heterogenous and that skeletal muscle tissue may be a source for pluripotent stem cells. 7,9,[24][25][26][27][28][29] In particular, stem cell populations from muscle were recently shown to reconstitute the hematopoietic compartment of lethally irradiated mice and to partially restore the expression of dystrophin in the mdx mouse, an animal model of Duchenne muscular dystrophy. 7 In our laboratory, we have shown that the population of MDC (pp6) was, in fact, multipotent and had the capability of differentiating into other mesenchymal tissues, such as osteogenic lineage.…”
Section: Introductionmentioning
confidence: 99%
“…For example, reserve stem cells derived from bone marrow can differentiate into neurons and glia (Eglitis and Mezey, 1997;Kopen et al, 1999), restore dystrophin expression in skeletal muscle (Gussoni et al, 1999), serve as a source of hepatic oval cells (Petersen et al, 1999), provide cells for neovascularization (Asahara et al, 1999;Kalka et al, 2000), and restore cartilage, bone, and fat (Pittenger et al, 1999;Prokop, 1997;Yoo et al, 1998). Conversely, stem cells derived from neural tissues (Bjornson et al, 1999) and muscle tissues (Jackson et al, 1999) can differentiate into blood. Furthermore, reserve stem cells derived from dermis can differentiate into skeletal muscle, fat, cartilage and bone (Young et al, 1999).…”
mentioning
confidence: 99%
“…these cells could be coaxed to differentiate into cells not normally associated with their 'committed' state) [12]. Examples include HSC that reputedly develop into neural, myogenic and hepatic cell types; neural or skeletal muscle stem cells that develop into the hematopoietic lineage [12][13][14][15][16][17][18]; and stromal stem cells that differentiated into cardiac muscle cells (myocytes) [19]. The reputed trans-differentiation potential and increased developmental potential of most of these adult stem cells has, however, been challenged [20][21][22][23].…”
Section: Stem Cells and Their Potential Role In Therapeuticsmentioning
confidence: 99%